Pain management for blunt thoracic trauma: A joint practice management guideline from the Eastern Association for the Surgery of Trauma and Trauma Anesthesiology Society. Issue 5 (November 2016) - Galvagno, Samuel Michael; Smith, Charles E.; Varon, Albert J.; Hasenboehler, Erik A.; Sultan, Shahnaz; Shaefer, Gregory; To, Kathleen B.; Fox, Adam D.; Alley, Darrell E.R.; Ditillo, Michael; Joseph, Bellal A.; Robinson, Bryce R.H.; et al.
Abstract : INTRODUCTION: Thoracic trauma is the second most prevalent nonintentional injury in the United States and is associated with significant morbidity. Analgesia for blunt thoracic trauma was first addressed by the Eastern Association for the Surgery of Trauma (EAST) with a practice management guideline published in 2005. Since that time, it was hypothesized that there have been advances in the analgesic management for blunt thoracic trauma. As a result, updated guidelines for this topic using the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) framework recently adopted by EAST are presented. METHODS: Five systematic reviews were conducted using multiple databases. The search retrieved articles regarding analgesia for blunt thoracic trauma from January1967 to August 2015. Critical outcomes of interest were analgesia, postoperative pulmonary complications, changes in pulmonary function tests, need for endotracheal intubation, and mortality. Important outcomes of interest examined included hospital and intensive care unit length of stay. RESULTS: Seventy articles were identified. Of these, 28 articles were selected to construct the guidelines. The overall risk of bias for all studies was high. The majority of included studies examined epidural analgesia. Epidural analgesia was associated with lower short-term pain scores in most studies, but the quality and quantity of evidence were very low, and no firm evidence of benefit or harm was found when this modality was compared with other analgesic interventions. The quality of evidence for paravertebral block, intrapleural analgesia, multimodal analgesia, and intercostal nerve blocks was very low as assessed by GRADE. The limitations with the available literature precluded the formulation of strong recommendations by our panel. CONCLUSION: We propose two evidence-based recommendations regarding analgesia for patients with blunt thoracic trauma. The overall risk of bias for all studies was high. The limitations with the available literature precluded the formulation of strong recommendations by our panel. We conditionally recommend epidural analgesia and multimodal analgesia as options for patients with blunt thoracic trauma, but the overall quality of evidence supporting these modalities is low in trauma patients. These recommendations are based on very low-quality evidence but place a high value on patient preferences for analgesia. These recommendations are in contradistinction to the previously published Practice Management Guideline published by EAST.